2012
DOI: 10.1080/17457300.2011.628752
|View full text |Cite
|
Sign up to set email alerts
|

Under-reporting of road traffic crash data in Ghana

Abstract: Having reliable estimates of the shortfalls in road traffic crash data is an important prerequisite for setting more realistic targets for crash/casualty reduction programmes and for a better appreciation of the socio-economic significance of road traffic crashes. This study was carried out to establish realistic estimates of the overall shortfall (under-reporting) in the official crash statistics in Ghana over an eight-year period (1997-2004). Surveys were conducted at hospitals and among drivers to generate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 3 publications
2
34
0
Order By: Relevance
“…The Africa region currently has some of the world's highest traffic injury rates, with road users such as motorcycle riders bearing a disproportionate share of the injury burden. Moreover, these injuries are often underreported and underestimated from current data [3, 4]. …”
Section: Introductionmentioning
confidence: 99%
“…The Africa region currently has some of the world's highest traffic injury rates, with road users such as motorcycle riders bearing a disproportionate share of the injury burden. Moreover, these injuries are often underreported and underestimated from current data [3, 4]. …”
Section: Introductionmentioning
confidence: 99%
“…Those who are killed or injured, in many cases, appear to go unreported because many people accept the tragedy of a crash as predestined. Identifying priority action areas and evaluating the effectiveness of measures used to improve safety are important steps in a comprehensive reporting system (Salifu and Ackaah 2009). The current research has offered additional insight into understanding belief-based factors related to nonreporting of road crashes that may assist in identifying priority action areas in Pakistan.…”
Section: Discussionmentioning
confidence: 97%
“…However, one efficient way to rapidly improve the availability of injury statistics is to make creative use of non-traditional information sources. In this essay, we illustrate this approach for Ghana, where Salifu et al 1 have shown substantial under-reporting of injuries in official statistics.…”
mentioning
confidence: 99%